Synthesis of nontronite and other Fe-rich smectites: a critical review. (December 2017) - Petit, S.; Baron, F.; Decarreau, A.
Abstract: The synthesis of clay minerals has been studied for decades in an attempt to better understand their formation in natural environments and more recently to obtain clay minerals with controlled compositions and properties. Even though nontronite has been synthesized successfully since 1935, the process is not a straightforward and has been poorly documented. In the present review concerning the synthesis of nontronite and other Fe-rich smectites, the experiments attempted in the past are discussed critically in light of the most recent data. Most notably, the application of relationships established recently, thanks to synthetic smectitic series, have allowed us to refine the chemical compositions of some nontronites synthesized previously.